Hindered cytoplasmic diffusion of inositol trisphosphate restricts its cellular range of action - Dickinson, George D. (Sci Signal, 2016)
The range of action of intracellular messengers is determined by their rates of diffusion and degradation. Previous measurements in oocyte cytoplasmic extracts indicated that the Ca(2+)-liberating second messenger inositol trisphosphate (IP(3)) diffuses with a coefficient (~280 μm(2) s(−1)) similar to that in water, corresponding to a range of action of ~25 μm. Consequently, IP(3) is generally considered a ‘global’ cellular messenger. We re-examined this issue by measuring local IP(3)-evoked Ca(2+) puffs to monitor IP(3) diffusing from spot photorelease in neuroblastoma cells. Fitting these data by numerical simulations yielded a diffusion coefficient (≤10 μm(2) s(−1)) about 30 fold slower than previously reported. We propose that diffusion of IP(3) in mammalian cells is hindered by binding to immobile, functionally inactive receptors that were diluted in oocyte extracts. The predicted range of action of IP(3) (<5 μm) is thus smaller than the size of typical mammalian cells, indicating that IP(3) should better be considered as a local rather than global cellular messenger.